Pelatihan Siswa MI Dalam Menggunakan The Power of Bottle Cap Untuk Operasi Hitung - Hartiningrum, Esty Saraswati Nur; Maarif , Safiil (Community Education Engagement Journal, 2023)
Class V mathematics learning includes addition and subtraction of integers. Especially for mathematics in elementary schools, mathematics is useful for equipping students with critical and creative attitudes. Mathematical concepts which are always abstract are presented with concrete and then semi-concrete things which then lead to the abstraction. Problems that arise in the integer system for class V students, especially at MI Al Hikmah Janti Jogoroto Jombang, are when students will perform arithmetic operations such as: 4 + (-7); -6 + 9; -3 – (-6); 2 – 7 and so on. The problems that arise in relation to these questions are how to provide explanations and how to instill the understanding of integer operations in a concrete way. The power of bottle cap is a simple visual aid that can be interesting, fun and inspire students in the learning process. The implementation stage of this service is to provide motivation and assistance in demonstrating the media. The result is training on the use of The power of bottle cap as a teaching aid to simplify arithmetic operations on integers. Students can understand the addition of integers quickly. The students were enthusiastic about using The power of bottle cap props and exploring the props with various types of questions.